دراسة كيميائية لبذور المشمش والإكيدنيا - محمد, رامز (Latakia University Journal -Biological Sciences Series, 2019)
هدف هذا البحث إلى دراسة التركيب الكيميائي لبذور المشمش والإكيدنيا، ومعرفة مواصفات الزيت الفيزوكيميائية، وتركيبه من الأحماض الدهنية، وقد أظهرت النتائج المتحصل عليها أنّ بذور المشمش تمتلك قيمة غذائية أعلى من بذور الإكيدنيا، حيث احتوت على نسبة (46.8%، 22.19%) من الزيت والبروتين على التوالي. أما بذور الإكيدنيا فقد احتوت على نسب أعلى من النشا والسكريات بلغت (13.4%، 9.52%) على التوالي، وعلى آثار من الزيت، ونسبة أقل بكثير من البروتين. تميز زيت بذور المشمش بقيم حموضة وبيروكسيد منخفضة مقارنةً بباقي الزيوت الغذائية (0.76 مغ KOH/غ، 4 ميللمكافئ/كغ) حموضة وبيروكسيد على التوالي. أخيراً بلغت نسبة حامض الأولييك (62.56%) مما يجعله زيتاً ملائماً من الناحية الغذائية. This research aims to study a gross chemical composition of apricot and loquat seeds, and to know the physicochemical characteristics of apricot seed oil and its fatly acid composition. The data indicated that apricot seeds had higher nutritive value than loquat seeds, and it contained (46.8%, 22.19%) protein and oil percentages, respectively, while loquat seeds contained higher amounts of starch and sugars which reached (9.52%, 13.4%) respectively. It also contained a trace amounts of oil and a protein percentage much lower than apricot seeds. Apricot seed oil possessed low peroxide and acid values in comparison to many edible oils, (4 meg/kg, 0.76 mg/g) respectively. Finally, oleic acid percentage reached (62.56%) which gives this oil excellent dietetic properties.